Irrigation of pear (A review) - Nemeskéri, E. (International Journal of Horticultural Science, 2009)
The plantation of intensive growing orchards and steady increase in yield is essential to return the growing cost by sale. Seasonal crop fluctuation of pear is increased by the frequently occurrence of drought and climatic changes. This study reviews genetic and growing factors determined the alternancy of pear and present the new knowledge concerning on water saving irrigation techniques. Use of dwarfing rootstocks, root pruning, branches pruning and new water saving irrigation make the changes in vegetative and generative growth that successfully improve the alternancy of pear growing. According to publications BA 29 of clonal quince rootstocks exhibited the best protection mechanism against to drought. Regulated deficit irrigation (RDI) applied during rapid shoot growth and slowly fruit growth result a decrease in shoot growth and 60% of water saving in pear orchard while there was no influence on harvested yield. Partial rootzone drying (PRD) microjet irrigation applied in pear orchard result 23-52% of decrease in water use, however concerning explorations are contradictory. Further investigations need to improve the efficiency of new irrigation technology adapted pear varieties based on monitoring of soil water status and measurement of stem water potential as stress indicators of plants.